Physical Analysis of Mount Talang â West Sumatera Activity Based on The Spectral Characteristics and Hypocenter Estimation of Volcanic Earthquakes - Welayaturromadhona, Welayaturromadhona; Susilo, Adi; Triastuty, Hetty (Physics Student Journal, 2013)
Volcanic activity of Mount Talang â West Sumatera is very interesting to be studied and to be learned, because its activity was influenced by geological structures in the vicinity of Mount Talang which is a depression zone of Sumatera Fault. This study aimed to investigate the characteristics of volcanic earthquakes at Mount Talang in the period of January to March 2013 based on the spectral analysis and hypocenter analysis. In addition, the velocity estimation was carried out to determine the value of the corresponding seismic wave velocity in the vicinity of Mount Talang. Volcanic earthquake signals obtained from four seismic stations Gabuo,Ketah, Puncak and Kopi. The seismic signals are selected first and then grouped by the type of the earthquake. Spectral analysis is performed to determine the value of the dominant frequency and the cut-off frequency (corner frequency) of volcanic earthquakes. Hipocenter analysis aims to determine the hipocenter depth of vulcanic earthquake. Based on the spectral analysis, the frequency content of volcanic earthquakes ranged from 3.12 to 17.87 Hz. The high frequency content can be correlated with geological structures in the vicinity of Mount Talang which is in the form of cracks / faults as a manifestation of the Great Sumatera Fault zone. Based on a formula which is known before, it can be seen that the estimation of rupture length is ranged between 67 to 142 m. The hypocenter distribution of volcanic earthquakes ranged from 2 to 9 km below the summit of Mount Talang. Based on the results of seismic wave velocity estimation that fits around Mount Talang is at the velocity between 2.5 to 2.8 km / s. Where the condition of the surrounding medium is still relatively compact.